Factors associated with life satisfaction in Asia / Ngoo Yee Ting - Ngoo, Yee Ting (2017)
Life satisfaction is a measure of well-being, and is defined by one's evaluation of life as a whole, rather than one's current feelings and emotions. It measures one's satisfaction with relations with others (especially with friends and family members) and with achieved goals, and feeling of self efficacy and being in control. The dominant concepts and theories of life satisfaction are Easterlin relative income theory, conceptual reference theory, hedonic adaptation theory and set point theory. These theories are built mostly from the European perspectives. This study set out to explore the correlates of life satisfaction from Asian perspectives and to have better understanding of the factors affecting life satisfaction in Asia. Life satisfaction is analysed by examining the mean values and distribution of the life satisfaction score, ranging from least satisfied to most satisfied. Life satisfaction mean was calculated from Asia Barometer surveys which cover 16 domains of life aspects. The results show that income is an important determinant after standard of living and the role of government to affect Asian’s life satisfaction. Asians are facing issues related to government policies which affect their life satisfaction such as corruption, inequality and unstable political conditions. Thus good governance is crucial for improving life satisfaction in Asia. An analysis of data from 28 Asian countries shows life satisfaction in each country is influenced by the characteristics, cultures and beliefs. Government should have a wider perspective in policy making besides making economic growth as the country’s objective or planning purpose. Policies should aim at improving the standard of living and governance. An improved life satisfaction would surely improve not only the well-being of people but also productivity and economic growth.